2018
DOI: 10.1051/cagri/2018006
|View full text |Cite
|
Sign up to set email alerts
|

Using social network analysis to evaluate the impacts of the research: on the transition to organic farming in the Camargue

Abstract: Évaluer les impacts des recherches en agriculture sur la société : outils, méthodes, études de cas. Abstract -This paper evaluates the relevance of undertaking a Social Network Analysis (SNA) to better understand the role played by the network of actors during innovation processes as well as validate stakeholders' views on actors' relationships in a case study on the transition to organic farming in the Camargue territory (South of France). The SNA method is part of a set of methods that forms an approach that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
8
0
3
Order By: Relevance
“…It would be particularly important to collect systematic data on relationships at different periods during network development, a task which could be conducted in quasi-real time or retrospectively. The latter option requires that actors remember what happened in the past, but this can work when the network of actors is relatively small and if additional information is requested in order to increase the level of thinking when defining relationship intensity scores [34]. The recommendation to collect network data over time to better account for the resilience of systems is supported by Janssen et al [72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be particularly important to collect systematic data on relationships at different periods during network development, a task which could be conducted in quasi-real time or retrospectively. The latter option requires that actors remember what happened in the past, but this can work when the network of actors is relatively small and if additional information is requested in order to increase the level of thinking when defining relationship intensity scores [34]. The recommendation to collect network data over time to better account for the resilience of systems is supported by Janssen et al [72].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that such innovations can develop with the help of complex relationships between actors, learning synergies, knowledge and techniques [31][32][33][34]. This implies a need for knowledge brokers to strengthen actors' relationships [35].…”
Section: The Contribution Of Network Analysis To Value Chain Assessmentmentioning
confidence: 99%
“…There is also the argument that countries need to use IT to eradicate knowledge divide to attain their development goals (Avgerou and Walsham, 2017;Sahay and Mukherjee, 2015;Ezema, 2013). These are coupled with the notion that access to, and use of, context-specific scientific knowledge are crucial to attaining every country's development goals (Quiedeville et al, 2018;Shuvia and Taisir, 2016;Nwagwu, 2013). These conditions reinforce the urgent need to create open access to scientific knowledge and educational resources created by universities in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A specific focus was to understand the nature and intensity of the links between stages, in order to better determine the role of the research undertaken. In addition, an analysis of the social network made it possible to examine the real role played by different research institutes in the transition to organic agriculture and, as a result, validate the actors' statements (Quiédeville et al, 2018).…”
Section: Recreating the Impact Pathway Of The Innovation In A Particimentioning
confidence: 99%